2021
DOI: 10.1097/qai.0000000000002680
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Testing and the Impact of the Pandemic on the Miami Adult Studies on HIV Cohort

Abstract: Background: Socioeconomic disadvantages and potential immunocompromise raise particular concerns for people living with HIV (PLWH) and other marginalized communities during the COVID-19 pandemic. In this study, we explored COVID-19 testing and the impact of the pandemic among participants from the Miami Adult Studies on HIV cohort, predominantly composed of low-income minorities living with and without HIV. Methods: Between July and August 2020, a telephone survey was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…The data presented in this study was collected between May 2020 and March 2021, and is likely not representative of usual patterns of substance misuse among C3PNO participants. Changes to the drug supply, such as decreased availability and quality along with increased costs have been reported by PWUD ( Ali et al, 2021 , Tamargo et al, 2021 ). For instance, cocaine use in the MASH cohort (a C3PNO cohort) declined by more than half during the early months of the pandemic ( Tamargo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data presented in this study was collected between May 2020 and March 2021, and is likely not representative of usual patterns of substance misuse among C3PNO participants. Changes to the drug supply, such as decreased availability and quality along with increased costs have been reported by PWUD ( Ali et al, 2021 , Tamargo et al, 2021 ). For instance, cocaine use in the MASH cohort (a C3PNO cohort) declined by more than half during the early months of the pandemic ( Tamargo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Changes to the drug supply, such as decreased availability and quality along with increased costs have been reported by PWUD ( Ali et al, 2021 , Tamargo et al, 2021 ). For instance, cocaine use in the MASH cohort (a C3PNO cohort) declined by more than half during the early months of the pandemic ( Tamargo et al, 2021 ). Therefore, some substances may have been less frequently used during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that examined substance use among PLWH during early COVID-19 reported variable results with no consistent pattern. Some studies reported increases in alcohol consumption [38,61] and other drug use [44], although it is unclear if these increases differed from those of people not living with HIV. Counter to expectations, some studies reported reductions in drug use among PLWH, including tobacco consumption [50,61].…”
Section: Substance Usementioning
confidence: 99%
“…Some studies reported increases in alcohol consumption [38,61] and other drug use [44], although it is unclear if these increases differed from those of people not living with HIV. Counter to expectations, some studies reported reductions in drug use among PLWH, including tobacco consumption [50,61]. There is also mixed evidence for increased adverse consequences from COVID-19 that are expected with increased substance use.…”
Section: Substance Usementioning
confidence: 99%
“…COVID-19 testing serves as an important complementary measure to prevent and control spikes in SARS-CoV-2 cases, enabling disease diagnosis and tracing the con rmed cases. [49][50][51][52][53][54] Nearly 160 million tests have been performed in China, as of August 6th, 2021. 55 Since studies on the willingness to be tested and actual uptake of COVID-19 tests are scarce, updated estimates can help identify the population subgroups to be targeted by health education interventions in China.…”
Section: Introductionmentioning
confidence: 99%